Penerapan Teori Belajar Humanistik Carl Rogers Bagi Siswa dengan Kurikulum Merdeka di Sekolah Dasar - Winata, Septiany Putri; Stiyaningsih, Wiky (Jurnal Konseling dan Psikologi Indonesia, 2025)
An effective curriculum is a curriculum that can adapt to the times and has a significant impact on improving the quality of education. This concept is closely related to learning theories, which are an integral part of the educational process, one of which is humanistic learning theory. The method used in this article is a literature study. This study uses a literature study by searching for data related to the research topic from various article sources. Data was obtained through Publish or Perish according to the topic, namely the application of humanistic theory for students with the Merdeka Belajar curriculum in Elementary Schools. Furthermore, the sources collected were 200 articles, after which identification was carried out, 16 articles were obtained that were in accordance with the research topic. Based on the results of the study with literature analysis of the Merdeka Curriculum in Elementary Schools, the Merdeka Belajar concept is very relevant and in line with the objectives and implementation of the curriculum which emphasizes flexibility, freedom to learn, and adjustments to student needs in the learning process.